2021
DOI: 10.1016/j.omto.2021.01.008
|View full text |Cite
|
Sign up to set email alerts
|

LINC00461 facilitates HNSCC development and reduces chemosensitivity by impairing miR-195-mediated inhibition of HOXA10

Abstract: Homeobox A10 (HOXA10) has been regarded to serve as an oncogene in head and neck squamous cell carcinoma (HNSCC). This study was intended to explore the interaction among the long intergenic noncoding RNA 00461 (LINC00461), microRNA (miR)-195, and HOXA10, and to investigate its role in epithelial-mesenchymal transition (EMT) and chemoresistance in HNSCC. The effects of LINC00461, miR-195, and HOXA10 on the EMT and chemoresistance of HNSCC cells were analyzed by comprehensive analysis of gain- and loss-of-funct… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 44 publications
0
6
0
Order By: Relevance
“…Our bioinformatics results also showed that miR-195-5p might be a tumor suppressor gene in lung cancer [ 13 ], and our in vitro experiments were consistent with previous results in non-small-cell lung cancer [ 23 ]. Guan et al reported that HOXA10 mediated EMT in head and neck squamous cell carcinoma and was targeted by miR-195-5p [ 24 ]. However, their effects on radiosensitivity were to be investigated.…”
Section: Discussionmentioning
confidence: 99%
“…Our bioinformatics results also showed that miR-195-5p might be a tumor suppressor gene in lung cancer [ 13 ], and our in vitro experiments were consistent with previous results in non-small-cell lung cancer [ 23 ]. Guan et al reported that HOXA10 mediated EMT in head and neck squamous cell carcinoma and was targeted by miR-195-5p [ 24 ]. However, their effects on radiosensitivity were to be investigated.…”
Section: Discussionmentioning
confidence: 99%
“…Some studies have demonstrated the involvement of lncRNAs in the metabolism and disposition of anti-cancer drugs, influencing directly the development of DR ( 142 , 148 ). In HNSCC, DR has become an increasingly concerning challenge for the scientific community and clinicians ( 16 , 31 , 135 ). Along with many others, the long intergenic non-coding RNA 00958 (LINC00958) has been studied as apoptosis- and autophagy-related lncRNA in HNSCC as part of prognostic signature, establishing a worse overall survival rate of patients when the signature is present ( 140 , 150 ).…”
Section: Lncrnas In Drug Resistance Mechanismsmentioning
confidence: 99%
“…showed that the upregulation of LINC00461, LINC00402, and SFTA1P had suppressive effects on the homologous pleckstrin-homology (PH)-domain leucine-rich-repeat protein phosphatases (PHLPP2), reported previously as a tumor suppressor in colon cancer ( 210 ). In HNSCC, LINC00461 was highly expressed in 52 tissues analyzed, and it was found that LINC00461 downregulates the expression of miR-195 to subsequently upregulates the expression of HOXA10, promoting EMT and enhancing chemoresistance in HSNCC ( 16 ).…”
Section: Lncrnas In Drug Resistance Mechanismsmentioning
confidence: 99%
See 1 more Smart Citation
“…Although LINC00461 is related to several types of cancers, the role of LINC00461 in breast cancer is not fully understood [21][22][23] . Here, we demonstrated that LINC00461 was overexpressed in TNBC and was required for glucose metabolism and progression of proliferation in TNBC.…”
Section: Introductionmentioning
confidence: 99%